Contrebandiers de monnaie et autorités locales sur les côtes basques au début du XVIIe siècle - Susana Truchuelo García (Criminocorpus)
The smugglers of money played an important role on the Basque coasts at the beginning of the XVIIth century. The illegal exit of money outside Castile, through the provinces of Biscay and Guipuzcoa and the entrance to fraud of counterfeit billons resulting from France, both by the passage of Irun and by the Basque ports, established their main activities, favored by the local tax statuses. The repression of this illicit trade put in competition the local authorities and police captains sent by Philippe III and Philippe IV, who so participated in the construction of the image of the smuggler of money.